Law and Development in West and Central Africa OHADA - Winship, Peter (SMU Dedman School of Law Legal Studies Research Paper, 2015)
This seminar paper considers whether OHADA - an experiment in unifying business law in African countries - has been a success. Following a prologue that explains the origins of the paper, the first part of the paper sets out basic information about the Organisation pour l’Harmonisation du Droit des Affaires en Afrique (“Organization for the Harmonization of Business Law in Africa,” known by the acronym OHADA). This part is followed by a review of law and development literature to assess the value of this literature for an evaluation of the success (or not) of OHADA. A third part then focuses on one specific uniform law, the law of secured transactions. The paper concludes that notwithstanding challenges the OHADA institutions exist and have produced uniform business laws for the formal business sector. Whether OHADA has been the cause of increased investment and trade requires studies that have not been carried out.
Keywords: African law; Secured transactions; commercial law; law and development; law reform; unification of law

Toward an Elaboration of a More Pluralistic Legal Landscape for Developing West African Countries: Organization for the Harmonization of Business Law in Africa (OHADA) and Law and Development - Hiez, David; Menétrey, Séverine (The Law and Development Review, 2015)
In Europe and especially in France, the African business law landscape, as well as the legal discourse, for developing West African countries is almost exclusively dedicated to OHADA, the Organization for the Harmonization of Business Law in Africa, created in 1993. While economic development in the Member States is the obvious underlying reason for the modernization and unification of African business law, the exact nature of such development remains uncertain, as does the manner in which a such result can or will be achieved. OHADA’s Uniform Acts are, with some minor exceptions, a carbon copy of French business law. The only goal is to increase international investment, which, in turn, is expected to generate economic development, but all without taking any notice of equality or social justice issues. That, without a doubt, is the reason why OHADA is constantly criticized as a law that benefits foreign investors, while remaining ineffective, even illusory, for local traders. To go beyond the criticism, the authors have decided to focus on the relationship between law and the informal sector and to draw lines between formal and informal rules in the business sector.
Keywords: Informal rules informal sector; OHADA (Harmonized Business Law in Africa); informal rules; informal sector

Business in West and Central Africa: The Legal Framework - an Introduction to the Laws of the OHADA - Hahn, Anne-Catherine; Darbellay Suso, Aline; Desax, Robert; Herzog, Sabine; Meyer, Manuel; Monnier, Philippe; Schnyder, Marion; Zemp, Rafael (Baker & McKenzie, 2015)

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (Working Together to Deliver - Sakha Sonke, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Accepted: 2016-11-08T12:11:22Z Artwork Medium: PDF Interview Medium: PDF
Keywords: Southern African Transport Conference; Transportation

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
http://erepository.uonbi.ac.ke/handle/11295/81712
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

Exploring shared governance as an alternative institutional model for the Southern African development community - Nyathi, Mkhululi (University of Pretoria, 2015)
The Southern African Development Community (SADC) was initially established as a coordination conference in 1980 and was transformed into a treaty organisation in 1992. Challenges of lack of coordination, inefficiency and lack of policy harmonisation led to the amendment of the Treaty in 2001. While the amendment of the Treaty served to address some of the challenges of the organisation, it failed to address the core challenge of the democratic deficit inherent in SADC s governance framework. While the SADC Treaty has as part of its principles and objectives the observance and promotion of democracy and the rule of law, both in its own processes and in its Member States, the design of the SADC institutions does not reflect these normative values. Governance of SADC is characterised by excessive executivism under the overarching powers of the Summit of Heads of State or Government. This democratic deficit is most prominently evidenced by the suspension and eventual disbandment of the SADC Tribunal, the only judicial organ of the organisation. The suspension and disbandment of the Tribunal, in addition to the obvious issue of legality that it raises since it was done in the absence of Treaty amendment, also raises the fundamental question of decision making in SADC in general, as the current treaty framework does not provide for meaningful conversation between and among the key institutions of SADC in matters involving policy formulation and implementation. There is also no institution with a strong oversight role in SADC. There is need for constitutional change in SADC if the organisation is serious in its commitment to achieve its objectives, which it has defined as its Common Agenda. This study proposes a treaty based reform process that is informed by the institutional model of shared governance. One of the several core tenets of this model is that in an organisation, there should be meaningful conversation among the internal stakeholders before a decision is made. For such conversation to be meaningful, there should be the broadest possible exchange of information among the components of an organisation. The proposals made by this study include transforming the Secretariat into an effective institution that formulates SADC laws and policies as well as their implementation frameworks; creation of a SADC parliament that would play a meaningful role on the amendment of the SADC Treaty and in the adoption of the budget; and an independent and accessible judicial body with significant powers of review. Shared governance as conceptualised in this study is not a substitute for, nor does it compete with related concepts like constitutionalism, separation of powers, the rule of law and participatory democracy, but in fact complements them. In addition to these proposals, there is a recommendation for the adoption of a robust access to information regime in which the shared governance institutional model would be anchored. There is also a recommendation for a new regime of law making through community legal instruments that would be directly applicable in Member States as opposed to the largely ineffective protocols.
URI: https://repository.up.ac.za/handle/2263/52280
Keywords: Civil society engagement; SADC; Southern African Development Community